A remote sensing-based assessment of gullies along main roads in Emakhazeni, Mpumalanga Province, South Africa - Loubser, M.J. (University of Pretoria, 2023)
Mini Dissertation (MSc (Environmental Management)--University of Pretoria, 2023.